A Comparison of Lifestyle Marketing and Brand Influencer Advertising for Generation Z Instagram Users. Issue 4 (19th May 2023) - Hazari, Sunil; Sethna, Beheruz N.
Abstract: Instagram has become a popular platform for consumers and marketers. Using the stimulus-organism-response theory, this study compared lifestyle and brand influencer types of Instagram advertisements to determine the impact on attention, attitude, and purchase intention for Gen Z Instagram users. The moderating role of gender and personality was also considered. Using MANOVA & Regression analysis, we found that males and extroverts had higher attention and attitude toward advertisements. No gender differences were found for brand influencer advertisements. The case for segmentation by personality over gender was more compelling. The findings of this study can help develop effective Instagram marketing campaigns.